Study the Relationship between Social Marketing Dimensions and Changing the Health Behavior of Ain Shams University Students Using Campaign of (Prevention is the Origin of the Tale) “A Field Study” - Desokey, Mohamed; Ragab, Gihan; Ahmed, Hanan (The Arab Journal of Administration, 2023)
The study aimed at: Study the relationship between social marketing dimensions and changing the health behavior of Ain Shams University students using campaign of Prevention is the origin of the tale. Approach of the study: The study based its design on the descriptive analytical approach to cause-and-effect relationships between variables. Methodology of the study: The survey forms were distributed to the sample of the study consisting of (384) individual students of Ain Shams University, and the selected awareness campaign were presented based on a Exploratory study on a soft sample of (25) individual students from Faculty of Business - Ain Shams University, in order to achieve the objectives of the study. The results of the study: The study found that there is a statistically significant relationship between (social product, social promotion, and social distribution) and changing the health behavior of Ain Shams University students, and that there is no statistically significant relationship between social pricing and changing health behavior, using campaign of (Prevention is the origin of the tale) subject of the study. Recommendations: The researcher recommends adding new dimensions of social marketing such as (opinion leaders dimension) in addition to conducting this study using other campaigns such as (campaign 100 million health, or awareness campaigns to prevent and reduce the spread of the new coronavirus (COVID-19).